A resuscitation ‘‘dilemma’’ theory–practice–ethics. Is there a theory–practice–ethics gap? - Mortell, Manfred (Elservier Ltd., 2009)
The theory–practice–ethics gap – a new paradigm to contemplate. Practices based on tradition, rituals and outdated information are placed into a nonscientific paradigm called the theory–practice gap. Within this paradigm there is often a gap between theoretical knowledge and its application in practice. This theory–practice gap has always existed [Allmark, P., 1995. A classical view of the theory– practice gap in nursing. J. Adv. Nurs. 22 (1), 18–23; Hewison, A. et al., 1996. The theory–practice gap in nursing: a new dimension. J. Adv. Nurs. 24 (4), 754–761]. Its creation is often sited as a culmination of theory being idealistic and impractical, even if practical and beneficial, are often ignored. Most of the evidence relating to the non integration of theory and practice makes the assumption that environmental factors are responsible and will affect learning and practice outcomes, hence the ‘‘gap’’. In fact, it is the author’s belief, that to ‘‘bridge the gap’’ between theory and practice an additional component is required, called ethics. A moral duty and obligation ensuring theory and practice integrate. In order to effectively implement new practices, one must deem these practices are worthy and relevant to their role as healthcare providers. Otherwise, we fall victims to providing nothing more than a lip service. This introduces a new concept which the author refers to as the theory–practice–ethics gap. This theory–practice–ethics gap must be considered when reviewing some of the unacceptable outcomes in health care practice. The author believes that there is a crisis of ethics where theory and practice integrate, and as a consequence, malfeasance. We are failing to fulfill our duty as healthcare providers and as patient advocates. One practice of major concern, which the author will endeavor to unfold relates to adult and pediatric resuscitation.